Pengembangan Aplikasi White Label PPOB berbasis Web menggunakan Pemodelan Reuse Oriented Development (Studi pada PT XYZ) - Andi Hafiidh; Herman Tolle; Welly Purnomo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Whitelabel is an activity that refers to buying a product/service by a reseller and then given a new label as if the reseller produced it. Meanwhile, payment point online bank (PPOB) is a bill payment system and products selling such as phone credit, phone quota, electricity tokens, electronic vouchers, etc. The background of this research is that currently there is one PPOB service provider in Indonesia, PT XYZ (the company name is obscured). PPOB PT XYZ has approximately 26,000 users, 17% of which are members owned by PT XYZ partners. PT XYZ opened a partnership with other companies / organizations to develop PPOB on behalf of the company / organization. This method is a marketing method called whitelabel. Although currently the PPOB whitelabel application with partners has been running well, but there are some new needs including adjustment of product profits, use of partner bank accounts, SMS notifications on PLN token purchases, and web-based PPOB applications. To be able to solve these new needs easily, quickly, and have a fairly good quality, the use of reuse oriented development methods is highly recommended. In this study a simple PPOB system was produced that could meet the new needs of PT XYZ's existing PPOB whitelabel, using a microservice structure and using a library (reusable component) and services from third parties (software as a service). The system gets 100% valid results on validation testing, also there are no critical issues in compatibility testing, and gets a score of 81.5% on user acceptance tests (UAT).